Predicting habitat suitability for the co-occurrence of an estuarine mesopredator and two top predatory fishes - Fontaine, Paco; Jensen, Christine C.; Matich, Philip; Rooker, Jay R.; Wells, R. J. David (Frontiers in Fish Science, 2024)
Determining habitat associations and co-occurrence patterns among species can provide insight into their behavior and shared roles in ecosystem function. This study used a long-term gill-net survey to investigate habitat associations and co-occurrence patterns of three predatory fishes in a large estuarine complex in the northwestern Gulf of Mexico including two top predators alligator gar (Atractosteus spatula) and bull shark (Carcharhinus leucas) and a mesopredator Atlantic stingray (Hypanus sabina). Habitat suitability models were used to assess habitat conditions under which multiple conspecifics or species co-occurred. Environmental drivers of habitat suitability differed within and across species, but salinity and temperature were the most influential variables. Intraspecific co-occurrence of both alligator gars and bull sharks were primarily observed between conspecifics of similar size in low-salinity waters, but intraspecific co-occurrence was higher for alligator gars than for bull sharks. Although sample size was low, intraspecific co-occurrence of Atlantic stingrays was frequent in open-water regions of the estuary and consisted of both juveniles and adults. Interspecific co-occurrence between alligator gars and bull sharks was primarily observed in habitats commonly used by both species, particularly in low-salinity regions of the estuary. Even though there may be confounding effects of sampling gear, interspecific co-occurrence of Atlantic stingrays with either alligator gars or bull sharks was limited, suggesting there was limited overlap in estuarine habitats or environmental conditions used by Atlantic stingrays relative to the two other species investigated. These results clarify the influence of abiotic and biotic variables on the distribution and abundance of these species and suggest potential areas where interactions between them may shape their roles as predators.